จุลินทรีย์ในดินที่มีฤทธิ์ยับยั้งเชื้อรา Curvularia sp. สาเหตุโรคเมล็ดด่างในข้าว SOIL MICROORGANISMS AND THEIR INHIBITION ON CURVULARIA SP.; FUNGAL PATHOGENS USING DIRTY PANICLE DISEASE IN RICE SEED - เนียมแสวง วาสนา (Srinakharinwirot University Journal of Sciences and Technology, 2021)
This study aimed to isolate actinomycetes and molds from soil for inhibiting Curvularia sp., a seed-borne pathogen of rice dirty panicle disease. Soil samples were collected from 10 agricultural areas included Tha Sao sub-district of Kanchanaburi Province, Prongmadua and Thungkraphanghom sub-district of Nakhon Pathom Province and Wangwa sub-district of Suphanburi Province. Total 50 actinimycetes were isolated and tested for their antifungal activity against Curvularia sp. by dual culture technique. Following antifungal activity testing, nine isolates exhibited inhibition against Curvularia sp., in which isolate CS40 showed the highest antifungal activity with 72.00% followed by isolate CS43 with 69.00% and isolate CS47 with 63.00%, respectively. Whereas 6 isolates had moderate to low antifungal activities. Only 6 isolates of molds, in which isolate SM05 and SF03 showed the highest antifungal activity with 75.00% followed by isolate SF06, SY02, SF02 and SL03 with 70%, 70%, 67.50% and 62.50%, respectively. Whereas 36 isolates had moderate to low antifungal activities.